2016
DOI: 10.18517/ijaseit.6.3.848
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pre-treatment Process of Cocoa Pod Husk Using Various Chemical Solvents

Abstract: The purpose of research is to see the effect of type of reagent (NaOH, H 2 O 2 and H 2 SO 4) and the condition of pretreatment of cocoa pod husk towards lignin content after pre-treatment and hydrolysis, reducing sugar and total sugar content. Response Surface Method (RSM) was used to optimize process conditions of pre-treatment (delignification). Hydrolysis for all pretreated sample were carried out using 3% H 2 SO 4 with a ratio of cocoa pod husk to solvent (1:10) for 2 hours at a temperature of 110 o C usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
2
14
2
Order By: Relevance
“…Pre-treatment of CPH has been carried out using chemicals, e.g., acidic or alkaline or organic solvents, to enhance the release of cellulose and obtain more fermentable sugars [43].…”
Section: Biofuels and Chemical Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-treatment of CPH has been carried out using chemicals, e.g., acidic or alkaline or organic solvents, to enhance the release of cellulose and obtain more fermentable sugars [43].…”
Section: Biofuels and Chemical Industrymentioning
confidence: 99%
“…Previous studies revealed that the lignin content of CPH reduced from 34% to 15% with the following alkali pre-treatment condition: 4% (w/v) NaOH, reaction time of 100 minutes with ratio of biomass/solvent of 1:25 (w/v) [43]. Mild organosolv protocol involves a relative short exposure to high concentration of butanol (95%), with acid (HCl) acting as a catalyst.…”
Section: Biofuels and Chemical Industrymentioning
confidence: 99%
“…This hydrolysis process using H2SO4 solution with 10% (v/v) of concentration yields the product with 9.89% (v/v) of glucose content. This result is quite smaller than Nazir et al study which cocoa pod husk was treated by the same acid solution yet with different concentration (1.5%w/v) resulting 15.59% of glucose content as reducing sugar [10]. Table 1.…”
Section: Resultsmentioning
confidence: 67%
“…Other important terms are the accuracy and variability of the models, which can be evaluated according to the R-Squared (R2) value which is between 0 to 1. If the value closer to1 means a better prediction of the response [16,17]. The R2 of the CCD models showed a higher value, which were 0.9801, 0.9936 and 0.9745 for COD, BOD, and Colour, respectively.…”
Section: Statistical Design Of Experimentsmentioning
confidence: 93%